The neuroscience of respect: insights from cross-cultural perspectives - Khalaila, Rabia; Dasgupta, Jayashree; Sturm, Virginia (Frontiers in Psychology, 2023)
Cultural values such as respect influence cognition, emotion, and behavior by modulating brain functioning. This mini-review discusses the cultural differences of respect as an essential human value, and the neural underpinnings accompanying them. Although neuroscientific studies are limited, we outline potential brain structures and networks that contribute to respect and use clinical examples to illustrate how behavior changes when these neural systems fail. A better understanding of the neuroanatomical basis of respect and its neural manifestations across cultures will help to advance current conceptualizations of the biology of human values.